Faktor yang Mempengaruhi Keputusan Pembelian Produk Fashion di Shopee - Vega Liana; Zuhrinal M.Nawawi (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Advances in technology have resulted in various developments in the corporate sector. Many companies now offer their goods through web applications. Shopee is one of the most popular online retail business applications today. The aims of this study were to: 1) determine the effect of product, price, promotion, distribution, people, process, and the physical environment on purchasing decisions for fashion products at Shopee, and 2) determine the effect of product, price, promotion, distribution, people, process. , and the physical environment for purchasing decisions for fashion products at Shopee for UINSU Medan students. The approach is quantitative. The participants in this study were UINSU Medan students who had used the Shopee application to shop for fashion items. The findings of this study indicate that product, price, promotion, distribution, people, process, and physical environment variables all influence the purchasing decision of fashion products at Shopee, and that product, price, promotion, distribution, people, process, and physical environment variables are all influence the purchasing decisions of fashion products at Shopee. greatly influenced the decision of UINSU Medan students to shop for fashion at Shopee. Keywords:Online Purchase Factor, Online Purchase Decision, Purchase Decision